Child health nurse perceptions of using confident body, confident child in community health: a qualitative descriptive study - Lyza N. Norton; Laura M. Hart; Francoise E. Butel; Shelley Roberts (BMC, 2020)
Abstract Background Confident Body, Confident Child (CBCC) is an innovative, evidence-based program providing parenting strategies to promote healthy eating, physical activity and body satisfaction in children aged 2-6 years. This study aimed to explore Child Health Nurse (CHN) experiences with using CBCC in their community health clinics with parents of young children. This work is part of a larger study involving tailoring, implementing and evaluating CBCC in a community child health setting. Methods This qualitative descriptive study was conducted within community child health centres at a public health service in Queensland, Australia. Participants included CHNs who had recently attended a tailored CBCC training workshop providing training/education, group activities/discussions and CBCC resources for CHN use in clinical practice. Semi-structured interviews were conducted to explore CHN perceptions of CBCC training, content and resources; and how CBCC was used in practice. Interviews were recorded and transcribed verbatim and analysed thematically. Results Eleven CHNs participated in interviews, with three themes emerging from the data. In Theme 1, High CHN satisfaction with CBCC messages, resources and utility, nurses expressed CBCC was highly valuable, useful and easy to enact in their practice. In Theme 2, Effects of CBCC on CHN knowledge, behaviour and practice, CHNs said they experienced increased awareness around body image, improved confidence in addressing issues with clients, and positive changes in their own behaviour and practice after attending CBCC training. In Theme 3, CHNs discussed Ideas for future implementation of CBCC, including challenges and considerations for practice, ongoing education/training for CHNs and broadening the target audience for wider CBCC dissemination. Conclusions This study found CHNs were highly accepting of CBCC as it was useful and valuable in practice, increased their awareness and confidence around body image issues, and positively affected their attitudes and behaviours. CHNs' suggestions for making CBCC delivery more efficient and broadening its reach in the community were valuable and will likely inform local policy and future research. Further research is required on the wider dissemination of CBCC to parents of young children for promoting positive body image and healthy eating, ultimately for the long-term prevention of eating disorders.